Do country stereotypes influence language learning motivation? A study among foreign language learners in Malaysia - Nikitina, Larisa (Institutionen for Moderna Sprak, Uppsala Universitet, 2019)
It has been acknowledged in research literature that stereotypes about a target language country held by language learners influence the students’ motivation to learn a foreign language (L2 motivation). However, there is a lack of studies that link explorations of these stereotypes and L2 motivation in a single research project. This mixed-methods study addressed this gap in research literature. It examined relationships between endogenous stereotypes about target language countries and L2 motivation using a sample of 194 students learning foreign languages in a major public university in Malaysia. These languages included French, German, Italian, Portuguese (European and Brazilian varieties), Russian and Spanish. The data were collected through a questionnaire survey. One open-ended question sought the students’ mental images of the target language countries; two thermometer-type scales assessed the students’ general attitudes toward the target language countries and people and 16 closed-ended statements with attached Likert-type scales assessed their L2 motivation. The findings from the qualitative strand of the analysis revealed that the respondents had distinct and predominantly positive images of each of the target language countries. This allowed making a tentative proposition that the country stereotypes would have a positive relationship with the students’ L2 motivation, especially the integrative orientation. Results of the statistical analyses in the quantitative phase indicated that the relationship between the country stereotypes and L2 motivation was the strongest in the case of the integrative orientation. The article concludes with a brief discussion of implications that can be drawn from this study.